Attenuation of ongoing neuropathic pain by peripheral acting opioid involves activation of central dopaminergic neurocircuitry - Vaidya S.; Shantanu P.A.; Tiwari V. (My University, 2025)
Background and purpose: Ongoing neuropathic pain is one of the most challenging clinical problems which have detrimental effects on a patient's life quality. Conventional therapies for chronic neuropathic pain majorly includes centrally acting analgesics. Unfortunately, the unceasing use of these drugs results in adverse effects, such as CNS in-coordination, respiratory depression and substance use disorder. DALDA ([D-Arg2, Lys4]-Dermorphin-(1–4)-amide), a peripherally acting opioid have been shown to possess potent analgesic activity without causing CNS toxicities in nerve-injured rats. However, the mechanism(s) underpinning DALDA induced-attenuation of ongoing neuropathic pain is yet to identify [1]. Experimental design: In this study, we have measured the in–silico ligand-receptor binding affinity of DALDA against potential inflammatory targets by utilizing glide module of schrödinger software. Effect of DALDA on oxido-inflammatory stress was evaluated in LPS-induced C6 glial cells. In-vitro studies were followed by the behavioral assessments, where effect of DALDA was measured in chronic constriction injured rats. To examine the effect of DALDA on dopaminergic neurotransmission, cerebrospinal fluid of nerve-injured rats was assessed using LC-MS/QToF (Liquid Chromatography-Mass spectrometry/ Quadrapole time of flight Analyzer). Results: DALDA has shown a good binding affinity with chemokine receptor type-2 (CCR2), chemokine CX3C receptor 1 (CX3CR1) and purinergic receptor (P2×4), major receptor subtypes involved in pain and inflammation. Findings from the in-vitro studies suggest that DALDA possesses potent anti-oxidant activity leading to inhibition of p38-MAPK pathway [1]. Moreover, the subcutaneous administration of DALDA leads to dose-dependent attenuation of thermal and mechanical hypersensitivity along with inhibition of neuroinflammatory mediators in serum and spinal cord of nerve-injured rats. Most importantly, DALDA treated neuropathic rats showed a preference for the DALDA-treated chamber, which was attenuated on pre-treatment with dopaminergic receptor antagonist, flupenthixol. LC-MS analysis further confirms the enhanced dopaminergic transmission in the brain of DALDA-treated neuropathic rats. Conclusion: Our findings suggest that DALDA mediated attenuation of ongoing neuropathic pain may be associated with a decrease in spinal neuroinflammatory signalling and subsequent increase in the brain dopamine level; may serve a potential therapeutic for the treatment of ongoing neuropathic pain. © 2021 Elsevier B.V.